Review and update of the Health of the Nation Outcome Scales for Elderly People (HoNOS65+). (17th September 2018) - James, Mick; Buckingham, Bill; Cheung, Gary; McKay, Roderick; Painter, Jon; Stewart, Malcom W.
Abstract : Aims and method: The Health of the Nation Outcome Scales for Elderly People (HoNOS65+) has been used widely for 20 years, but has not been updated to reflect contemporary clinical practice. The Royal College of Psychiatrists convened an advisory board, with expertise from the UK, Australia and New Zealand, to propose amendments. The aim was to improve rater experience when using the HoNOS65+ glossary by removing ambiguity and inconsistency, rather than a more radical revision. Results: Views and experience from the countries involved were used to produce a series of amendments intended to improve intra- and interrater reliability and improve validity. This update will be called HoNOS Older Adults to reflect the changing nature of the population and services provided to meet their needs. These improvements are reported verbatim, together with the original HoNOS65+ to aid comparison. Clinical implications: Formal examination of the psychometric properties of the revised measure is needed. However, clinician training will remain crucial. Declaration of interest: None.